Distribution and incidence of atoxigenic Aspergillus flavus VCG in tree crop orchards in California: a strategy for identifying potential antagonists, the example of almonds - Picot, A.; Doster, M.; Islam, M.; Callicott, K.; Ortega Beltran, A.; Cotty, P.J.; Michailides, T. (Elsevier, 2018)
To identify predominant isolates for potential use as biocontrol agents, Aspergillus flavus isolates collected from soils of almond, pistachio and fig orchard in the Central Valley of California were tested for their membership to 16 atoxigenic vegetative compatibility groups (VCGs), including YV36, the VCG to which AF36, an atoxigenic isolate commercialized in the United States as biopesticide, belongs. A surprisingly large proportion of isolates belonged to YV36 (13.3%, 7.2% and 6.6% of the total almond, pistachio and fig populations, respectively), while the percentage of isolates belonging to the other 15 VCGs ranged from 0% to 2.3%. In order to gain a better insight into the structure and diversity of atoxigenic A. flavus populations and to further identify predominant isolates, seventeen SSR markers were then used to genetically characterize AF36, the 15 type-isolates of the VCGs and 342 atoxigenic isolates of the almond population. There was considerable genetic diversity among isolates with a lack of differentiation among micro-geographical regions or years. Since isolates sharing identical SSR profiles from distinct orchards were rare, we separated them into groups of at least 3 closely-related isolates from distinct orchards that shared identical alleles for at least 15 out of the 17 loci. This led to the identification of 15 groups comprising up to 24 closely-related isolates. The group which contained the largest number of isolates were members of YV36 while five groups were also found to be members of our studied atoxigenic VCGs. These results suggest that these 15 groups, and AF36 in particular, are well adapted to various environmental conditions in California and to tree crops and, as such, are good candidates for use as biocontrol agents.